Estudio de factibilidad para la implantación de un semi-internado en la unidad educativa javier - Suárez M., Glenda (2009)
This Project Hill be done for the necessity of Guayaquil´s society that is looking to satisfy people´s needs because as time goes by the responsibilities acquired grow.This will be of great help for parents who are looking for the best education for their children, this will also be useful to fulfil the responsibilities of your children as students and to have the maximum in students scholar life a achievements. This project has the general objective to evaluate the economic factor to star semi-internal school “Unidad Educativa Javier”. The information presented is what is going to be needed for the project, it also details the financial situation, the profit, it also establishes the procedure and the time to recover the amount invested, an operational plan for marketing, according to the objective proposed. The project has its rentability, with its internal rate returns of 91,87% and the VNA of $50.701,46.